2009
DOI: 10.1016/j.jmatprotec.2008.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and numerical study of strain rate influence on AA5083 formability

Abstract: International audienceWith the application of new forming techniques (hydroforming, incremental forming), it is necessary to improve the characterization of the formability of materials and in particular the influence of strain rate. This paper begins with the characterization of material behavior of an aluminum alloy 5083 at high temperatures. To describe its visco-plastic behavior, Swift's hardening law is used and the corresponding parameter values are identified. Then, two different approaches are introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(50 citation statements)
references
References 19 publications
(19 reference statements)
0
50
0
Order By: Relevance
“…In recently years, a significant effort has been spent on developing more accurate and reliable analytical and numerical models to construct FLCs (Ref [8][9][10][11][12]. Also, several necking criteria have been proposed to predict the onset of localized necking and construct the FLCs of sheet metals, e.g., BrunÕs criterion (Ref 8), PetekÕs criterion (Ref 9), VolkÕs criterion (Ref 10), etc.…”
Section: Introductionmentioning
confidence: 99%
“…In recently years, a significant effort has been spent on developing more accurate and reliable analytical and numerical models to construct FLCs (Ref [8][9][10][11][12]. Also, several necking criteria have been proposed to predict the onset of localized necking and construct the FLCs of sheet metals, e.g., BrunÕs criterion (Ref 8), PetekÕs criterion (Ref 9), VolkÕs criterion (Ref 10), etc.…”
Section: Introductionmentioning
confidence: 99%
“…The upper parts of the curve show the areas occurring for the fracture in the sheet material. [11][12][13] Upon evaluating the forming-limit diagram in Figure 11, it is clear that the AA6061-T4 sheet material has higher deformation limits than the AA6019-T4 sheet material, by showing higher elongation behaviour than the latter. Thus, it provides that the forming-limit curve obtained for the AA6061-T4 sheet material was above the AA6019-T4 sheet metal's forming-limit curve.…”
Section: Forming-limit Diagrammentioning
confidence: 99%
“…10,11 The parameters of the deformation, such as the temperature and strain rate, affecting the mechanical properties of materials affect the formability of sheet material and therefore also affect the forming-limit diagrams. In their studies, C. Zang et al 12,13 determined, by analysing the FLDs of AA5086 and AA5083 aluminium alloys at elevated temperatures and at different strain rates, that the ability of formability decreases due to the increase in the strain rate. T. Naka et al 14 in their study looked at the 5083 magnesium-aluminium alloy at different temperatures and strain rates and reported that the strain rates decrease the formability at high temperatures, but a significant effect is not observed at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different failure criteria have been discussed by Zhang et al [3]. If the necking occurs in a zone, a sharp change of strain can be observed, corresponding to the onset of a plastic instability.…”
Section: Flc Identificationmentioning
confidence: 99%